Translating near-synonyms in the Quran: a semantic analysis of three near-synonyms and their English translations - Alduhaim, Asmaa (Penerbit Universiti Kebangsaan Malaysia, 2021)
This paper aims to explore how translators translate both the connotative and denotative meanings of nearsynonyms from the Quran into English language. The article will shed light on the phenomenon of near-synonymy, as well as its connotative and denotative meanings and how the translator’s background could have influenced their translation. There has been a dearth of attention on the translation of near-synonyms in the Quran; accordingly, this study examines three pairs of near-synonyms from the Quran and their particular translations in the following three English translations of the Quran itself: 1) The Koran Interpreted by Arberry; 2) The Quran: A New Translation by Abdel Haleem; and 3) The Sublime Quran by Bakhtiar. These translations were chosen due to the significant differences in style and translators’ backgrounds. The analysis aims to highlight the difference in meaning of each pair of near-synonyms by distinguishing both their connotative and denotative meanings. This will be followed by an examination of the translations to recognise whether the near-synonyms were accurately translated in these given instances or lost some, or even all, of their meaning during the translation process and discuss if translator’s background could have influence on it. Based on the discussion and analysis of these examples, it is evident that all three translations failed to distinguish between the pair of near-synonyms and to capture the accurate meaning throughout the Quran, leading to a semantic void. It is similarly clear that the linguistic complexity of the Holy Quran has created a challenging mission for translators, which has ultimately led to loss of accuracy and meaning. The results have shown that each translator chose their own approach based on their translational goal or their educational and personal backgrounds.